An SFL-oriented RARE Framework for the Teaching Reading in EFL Context - khoirotunisa, Latifah; Izzah, Lidiyatul; Hazrianthi, Nenden (English Language in Focus (ELIF), 2022)
The research aimed to find out the RARE (Review Answer Read Express) as an effective medium in teaching speaking. Based on the result of research on the population of students in class VIII Yayasan Al Muslim Tambun in the academic year 2019/2020 as the experimental class. The method in this research uses the random sampling technique which is used in class VIII. The mean of students’ post-test is higher than the pre-test. The average value of the post-test is 89.31and pre-test 62.04It also showed that the value of Tcal (2.55) is higher than Ttable (1.721) at the significance degree 5%. If the result of the t-test is higher than the t-table, the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. Based on the result of the t-test calculation above, since the positive hypothesis (Ha) was accepted, we can conclude that the RARE (Review Answer Read Express) technique is an effective medium in teaching reading.